Peningkatan Aktivitas Dan Hasil Belajar Matematika Melalui Implementasi Penilaian Portofolio Pada Siswa Kelas Viii Semester Genap Smp Muhammadiyah 1 Gatak(PTK di SMP Muhammadiyah 1 Gatak Tahun Ajaran 2015/2016) - Setyowati, Nuning, Dr. Sumardi, M.Si (2016)
The background of this study is caused by low activity and the result of studying math in VIII A class of SMP Muhammadiyah 1 Gatak. This study aims to describe the increasing of activity and result of studying math. The subject of this study are the students in VIII A class of SMP Muhammadiyah 1 Gatak in 2015/2016 academic year by implementation of portofolio assesment. This study belongs to classroom action research. The techniques of collecting data are observation, test, field note, and documentation. The result of this study showed the increasing of activity and the result of studying math. The increasing of studying math activity can be seen by: 1. the students can share their opinion before action research is 5 students (20,83%) after action research is 10 students (41,66%); 2. the students can ask to the teacher before classroom action is 4 students (16,57%) after classroom action is 11 students (45,83%); 3. the students can do the exercises before classroom action is 7 students (29,17%) after classroom action is 14 siswa (58,33%); 4. the students can do the homework before classroom action is 8 students (33,33%) after classroom action is 19 siswa (79,16%). The result of studying math can be seen by indicator that showed the students get the score upon criterion of minimum passing before classroom action is 6 students (25%) after classroom action is 16 students (66,67%). Based on the explanation above, it can be concluded that the implementation of portofolio assesment can increase activity and the result of studying math.